Billboards: Are They Here to Stay? A Study of Billboards in EDSA, Philippines - De los Reyes, Bernadette M.; Santos, Romeo B. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 3, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The landscape of Manila has cursorily changed in recent years and the streetscape is a visible text of these changes. One factor is the growing number of advertisements along major thoroughfares which have raised concerns of proliferation and the danger that comes with them. These outdoor advertisements or commonly called billboards are becoming an inherent part of our urban living and have evolved into a big industry that is difficult to disband. This initial stage of an on-going study looks at the aspect of this type of roadside visual pollution, its existing condition and situation in EDSA, Metro Manila. It will attempt to classify billboards and clarify the structure of the process and organization behind the business. Identification of deficiencies, problems, and possibilities in the existing laws, guidelines, and policies that govern its installation is also hoped to be done. The final stage of a future paper intends to formulate and advance a methodology of determining appropriateness of billboards.